AB1053 Neuropathic Pain in Rheumatic Patology. Evador Study. (10th June 2014) - Candelas, G.; Vidal, J.; Gobbo, M.; Tornero, J.; Perez-Vicente, S.
Abstract : Background: There is no relevant data on prevalence and management of neuropathic pain in the field of rheumatology. Its clinical impact and prognosis is worse than in case of nociceptive pain. All these aspects have been considered of interest and have been collected and specifically evaluated in the EVADOR study. Objectives: To study the prevalence of neuropathic pain in the rheumatology clinic, its characteristics and the treatment used for its management. Methods: Observational study with 2 phases (cross-sectional and prospective) of new patients (NP) or reviewed patients (RP) randomly selected and managed accordingly to usual clinical practice in 34 Spanish non monographic rheumatology services. The presence of neuropathic pain was assessed with the Spanish version of the DN4 questionnaire. A second follow-up visit was arranged for all patients with VAS pain ≥4 during the last week and for whom pain treatment had just been prescribed or for patients already receiving pain treatment for whom an analgesic change was expected. Exclusion criteria were: (a) physical, psychological or social problems preventing a reliable data collection (b) trauma pain not related to rheumatic disease. Variables collected: socio-demographic characteristics, VAS pain during the last week, Brief Pain Inventory (BPI), pattern and pain characterization, treatment prescribed (SF12), emotional state (HADS and Zung scale). The statistical analysis consisted on calculating the mean (SD) or the median (IQR) for the quantitative variables, and frequencies for the qualitative variables. To establish differences between groups student's t and chi-square statistics test were used. Results: Of the 1.084 patients in the EVADOR study, 166 (17%) complied with criteria for neuropathic pain (DN ≥4). Among them: 80% were women, 58% with 46-65 years old, 95% Spaniards, 79% living in urban areas, 37% active at work and 5% on medical leave. 64% of the patients had continuous pain with predominance at rest, 48% suffered pain overnight, 54% suffered pain during all day, 73% suffered breakthrough pain throughout the day. 73% of patients suffered a burning sensation, 45% felt a painful cold sensation, and 63% felt like electric shocks. Main symptoms were prickling and "pins and needles" (affecting 85% of patients in both cases), followed by numbness (69%) and stinging (43%). The most frequent sign was pain intensification by rubbing, hypoesthesia to touch (26%) or to puncture (11%). Treatments prescribed were mainly analgesics (64%), coadjuvants (39%), interventional techniques (10%) and non pharmacological treatments (8%). 19% of patients used other treatments. Pain intensity and quality of life significantly improved between the first and the second visit, although its clinical impact is higher than in the case of nociceptive pain (Table 1 ). Conclusions: Prevalence of neuropathic pain in rheumatology patients is significant (17%). Its presence indicates nervous system sensitization and its prognosis is worse. Management of these patients by the rheumatologist improves their pain and their quality of life. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.5957